2018
DOI: 10.1093/sleep/zsy104
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy for older adults with insomnia and depression: a randomized controlled trial in community mental health services

Abstract: CBT-I and CBT-I+ were both effective at reducing insomnia and depression severity for older adults. Mental health services that deliver treatment for comorbid insomnia with cognitive behavior therapy may improve recovery outcomes for older adults with depression. Trial Registration: Australian and New Zealand Clinical Trials Registry (ANZCTR); URL: https://www.anzctr.org.au; Trial ID: ACTRN12615000067572; Date Registered: December 12, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 53 publications
5
75
1
1
Order By: Relevance
“… 29 Cognitive behavior therapy has been shown to be effective at reducing insomnia and depression severity for older adults, and it has been demonstrated that mental health services can improve recovery outcomes for older adults with depression. 30 It is important to design interventions aimed at decreasing the effects of insomnia in surgical patients to improve their health and quality of life. The ever-increasing rate of sleep disorders means identifying modifiable risk factors is of the utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Cognitive behavior therapy has been shown to be effective at reducing insomnia and depression severity for older adults, and it has been demonstrated that mental health services can improve recovery outcomes for older adults with depression. 30 It is important to design interventions aimed at decreasing the effects of insomnia in surgical patients to improve their health and quality of life. The ever-increasing rate of sleep disorders means identifying modifiable risk factors is of the utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…The observed distributions in the insomnia were summarized in de ned groups based on the scores from ISI as follows: none (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), severe (22)(23)(24)(25)(26)(27)(28). Depression was rate on PHQ-9 of ve levels: none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderatesevere (15)(16)(17)(18)(19) severe (20)(21)(22)(23)(24)(25)(26)(27). Anxiety was graded according to the score of the GAD-7: none (0-4), mild (5-9), moderate (10-13), moderate-severe (14-18), severe (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavior therapy were both effective at reducing insomnia and depression severity for older adults. Mental health services were proved to improve recovery outcomes for older adults with depression [27]. It is important to design interventions aimed at decreasing the effects of poor sleep quality in surgical patients to support improving their health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, preliminary research has shown promising results. In one study, traditional CBTi, as well as CBTi with an added mood module both resulted in significant reductions in both insomnia and depression severity compared to a psychoeducation only control group [88]. Simiarly, research examining the effect of a mindfulness-based intervention found that improvements in insomnia symptoms were associated with reductions in depressed mood [89].…”
Section: Emerging Science In the Psychological Treatment Of Late-lifementioning
confidence: 99%